The physiological performance of offspring nursing from dams treated with different levels of sodium tungstat - Rasheed, Suha A. (The Iraqi Journal of Veterinary Medicine, 2012)
This study aimed to recognize the different effects of administration of sodium tungstate in developmental indices of the offspring till weaning. Four groups of Albino Wistar pregnant female rats were used, the first one was control while the remaining three groups intubated with Na- tungstate 75, 150 and 300 mg/ kg/ day respectively since the first day of parturition throughout 21 days. Results referred to an elevation in weight gain of rat dams treated with 75 mg/ kg while weight gain of offspring elevated in both doses of 75 and 300 mg/ kg throughout 21 days, teeth and eye orifice were observed in doses of 75 and 300 mg/ kg faster than control while the mean of ovary weight elevated in both 75 and 300 mg/ kg however the dose 300 mg/ kg revealed the less value of testes weight. The conclusion of present study is that Na- tungstate has positive effects on developmental indices in offspring when administered through nursing until weaning.